Stock Split Announcements and Their Impact on Shareholders' Wealth : A Study on the Indian Stock Market - Pradhan, Subhendu Kumar; Kasilingam, R. (Indian Journal of Finance, 2018)
The study attempted to find out the impact of stock split on shareholders' wealth. The samples were selected from 500 companies of S&P BSE 500 index. The study analyzed the impact by taking the share prices of sampled companies for 30 days before and 30 days after the stock split announcements. The market adjusted model was used for calculating the abnormal returns. The statistical tools such as paired sample t - test and analysis of variance were used for analysis. The study concluded that stock split did not affect the share prices as per the theoretical point of view, but in reality, it affected the share prices and increased trading volumes after split. The study alsoÂ concluded that stock split had an impact on shareholders' wealth, but this impact was not different according to the nature of the industry.